Construction of a La-ZnIn2S4/MIL-125(Ti) heterojunction for highly efficient photocatalytic degradation of aflatoxin B1. Issue 3 (13th January 2023) - Yang, Xiaobing; Pan, Junjie; Xing, Bingcong; Lei, Wenjie; Fu, Yingchun; Cheng, Kejun
Abstract : Nowadays, aflatoxin B1 (AFB1 ) contamination is considered as one of the most common food safety issues for humans and animals. Abstract : Nowadays, aflatoxin B1 (AFB1 ) contamination is considered as one of the most common food safety issues for humans and animals. As one of the most advanced oxidation techniques, photocatalytic degradation can break down organic contaminants into nontoxic and harmless materials efficiently. In this paper, we explored the degradation efficiency of AFB1 by ZnIn2 S4 . To promote the photocatalytic degradation efficiency of AFB1, ZnIn2 S4 was coupled with MIL-125(Ti) and then doped with La [this hybrid is denoted as La-ZnIn2 S4 /MIL-125(Ti)] to effectively convert it via photocatalytic generation of superoxide radicals (˙O2 − and ˙OH) and achieve much enhanced photocatalytic performance, which is demonstrated by degrading 97.6% of AFB1 . According to the transient photocurrent responses, the doping of La and coupling with MIL-125(Ti) can highly improve the efficient separation of the photoinduced electron–hole pairs on ZnIn2 S4, leading to the effective conversion of OH − and O2 into ˙O2 − and ˙OH, respectively, during the photodegradation process. This strategy of coupling with MOFs and doping with rare earth elements provides a facile and efficient method for degrading food pollutants produced by aflatoxins.